2022
DOI: 10.1021/acsaem.2c00303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermochemical Energy Storage Performance of Fe-/Mn-Doped, Zr-Stabilized, CaO-Based Composites under Different Thermal Energy Storage Modes

Abstract: CaCO3/CaO materials possess the advantages of low cost, high energy storage density, and working temperature, which offer these materials the potential to be used in thermochemical energy storage systems for concentrated solar power plants. However, CaCO3/CaO materials possess poor antisintering and optical absorption abilities, largely limiting their practicability for direct solar utilization. In this study, binary ion doping of Fe/Mn and Zr-based stabilizer incorporation were simultaneously conducted to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 52 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…It is worth mentioning that the spectral absorbance of materials in the metal oxide system is relatively positive, which is much higher than that of the CaCO 3 /CaO system which discussed this issue primarily. The optical absorption of pure CaCO 3 /CaO is about 11% from 300 to 2500 nm and remains very low in the whole wavelength range 4,34,48 . The sunlight absorption capacity can be roughly estimated through the color of samples, but there are still some differences in the specific absorbance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the spectral absorbance of materials in the metal oxide system is relatively positive, which is much higher than that of the CaCO 3 /CaO system which discussed this issue primarily. The optical absorption of pure CaCO 3 /CaO is about 11% from 300 to 2500 nm and remains very low in the whole wavelength range 4,34,48 . The sunlight absorption capacity can be roughly estimated through the color of samples, but there are still some differences in the specific absorbance.…”
Section: Resultsmentioning
confidence: 99%
“…Solar energy is the most abundant renewable energy and solar power generation technology can be divided into photovoltaic (PV) and concentrated solar power (CSP) 3 . CSP can be combined with efficient energy storage system to overcome the discontinuity of solar energy and achieve 24‐h electricity supply 4 …”
Section: Introductionmentioning
confidence: 99%
“…Reducing carbon emissions has become an international consensus to prevent global warming . CO 2 capture, utilization, and storage (CCUS) technology becomes a preferable option to achieve near-zero carbon emissions considering technical feasibility and investment cost. , Low cost and broad applicability make calcium looping (CaL) one of the most promising CCUS technologies. , Apart from the application in cyclic CO 2 capture, the CaO-based material also demonstrates the versatility of being used as the catalyst/absorbent in the sorption-enhanced hydrogen production , and heat carrier in the thermal chemical energy storage coupling with concentrating solar energy. , The common demand for the CaO-based material among the scenarios mentioned above lies in the cyclic durability and mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Apart from the application in cyclic CO 2 capture, the CaO-based material also demonstrates the versatility of being used as the catalyst/absorbent in the sorption-enhanced hydrogen production 7,8 and heat carrier in the thermal chemical energy storage coupling with concentrating solar energy. 9,10 The common demand for the CaObased material among the scenarios mentioned above lies in the cyclic durability and mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…16) Previous literature reported that most of the CaO-based adsorbents are suffered from a loss of adsorption uptake during the repeated cycle of the adsorption-desorption process because of the sintering. [17][18][19] The surface area and porosity of the adsorbent are continuously reduced during sintering, resulting in a lower CO 2 adsorption uptake. This phenomenon has sparked the interest of researchers striving to enhance the regenerating capabilities of CaO-based adsorbents.…”
Section: Introductionmentioning
confidence: 99%